2006
DOI: 10.2176/nmc.46.348
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal Subarachnoid Hemorrhage in a Patient With Human Immunodeficiency Virus Type 1 Infection-Case Report-

Abstract: A 54-year-old human immunodeficiency virus type 1 (HIV-1)-infected homosexual Japanese male was found to have collapsed in his bathroom and was brought to our facility with diminished level of consciousness. Computed tomography showed subarachnoid hemorrhage (SAH). He was severely dehydrated with unstable general status that deterred us from performing emergent surgery. Cerebral angiography performed on the 18th hospital day revealed bilateral distal anterior cerebral artery aneurysms. Clipping of these aneury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…In the pre-cART era, young adults and children with advanced HIV infection were known to develop a cerebral aneurysmal arteriopathy with fusiform dilatation and ectasia of the cerebral vessels, often in the Circle of Willis, with or without SAH. [45][46][47][48][49][50][51][52] Case reports of radiographic stabilization or resolution of aneurysms after initiation of cART 53,54 imply that immunodeficiency may have played a role in the development of these vascular abnormalities. More recently, Durand et al observed an increased adjusted hazard (HR 3.28, 95% CI 1.75-6.12, p < 0.001) of a composite outcome of ICH and SAH in HIV-infected individuals compared with uninfected age-matched controls using two validated medical databases for all residents of Quebec province between 1985-2007.…”
Section: Intracerebral and Subarachnoid Hemorrhage In Hiv-infected Inmentioning
confidence: 99%
“…In the pre-cART era, young adults and children with advanced HIV infection were known to develop a cerebral aneurysmal arteriopathy with fusiform dilatation and ectasia of the cerebral vessels, often in the Circle of Willis, with or without SAH. [45][46][47][48][49][50][51][52] Case reports of radiographic stabilization or resolution of aneurysms after initiation of cART 53,54 imply that immunodeficiency may have played a role in the development of these vascular abnormalities. More recently, Durand et al observed an increased adjusted hazard (HR 3.28, 95% CI 1.75-6.12, p < 0.001) of a composite outcome of ICH and SAH in HIV-infected individuals compared with uninfected age-matched controls using two validated medical databases for all residents of Quebec province between 1985-2007.…”
Section: Intracerebral and Subarachnoid Hemorrhage In Hiv-infected Inmentioning
confidence: 99%
“…У 36,4% больных детей и 37,5% взрослых пациентов до диагностики аневризм имели место инфаркты мозга. Наличие аневризмы у 45% пациентов детского воз-раста и 25% взрослых не сопровождалось ишемией и геморрагией [43,[53][54][55][56][57][58][59][60][61][62].…”
Section: геморрагические нарушенияunclassified
“…Until 2006, fusiform dilatations of intracranial arteries have been described in HIV-positive in 32 children 9,14,26,29 , and until 2007 only 11 HIV-positive patients have been described with intracranial aneurysms 17,18,20,29 . Seven of these had saccular aneurysms and one had a giant aneurysm 8,12,14 that could have been coincidental congenital aneurysms.…”
Section: Historymentioning
confidence: 99%
“…Infection with the HIV contributes to an increased risk of stroke 21 , and published series of HIV -positive patients demonstrated an incidence of 6-11% of intracerebral hemorrhage 2,13,17,20,21,22,23,24,27 .…”
Section: Epidemiologymentioning
confidence: 99%